2007
DOI: 10.1021/jm070441u
|View full text |Cite
|
Sign up to set email alerts
|

Cannabilactones: A Novel Class of CB2 Selective Agonists with Peripheral Analgesic Activity

Abstract: The identification of the CB2 cannabinoid receptor has provided a novel target for the development of therapeutically useful cannabinergic molecules. We have synthesized benzo[ c]chromen-6-one analogs possessing high affinity and selectivity for this receptor. These novel compounds are structurally related to cannabinol (6,6,9-trimethyl-3-pentyl-6 H-benzo[ c]chromen-1-ol), a natural constituent of cannabis with modest CB2 selectivity. Key pharmacophoric features of the new selective agonists include a 3-(1',1'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
110
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(116 citation statements)
references
References 57 publications
4
110
2
Order By: Relevance
“…For the cannabilactones, a series of cannabinol derivatives, differences in affinity results on mouse CB 2 R and human CB 2 R were reported [144,145]. The authors suggest the existence of different binding motifs of cannabilactones for the mouse or human CB 2 R [144]. This indicates one should be particularly careful interpreting rodent or human CB 2 R affinities.…”
Section: Affinity and Species Differencementioning
confidence: 98%
See 1 more Smart Citation
“…For the cannabilactones, a series of cannabinol derivatives, differences in affinity results on mouse CB 2 R and human CB 2 R were reported [144,145]. The authors suggest the existence of different binding motifs of cannabilactones for the mouse or human CB 2 R [144]. This indicates one should be particularly careful interpreting rodent or human CB 2 R affinities.…”
Section: Affinity and Species Differencementioning
confidence: 98%
“…For JTE-907, a hundred fold higher affinity for rat CB 2 R (K i CB 2 R = 0.4 nM) was described compared to human CB 2 R (K i CB 2 R = 36 nM) [120]. For the cannabilactones, a series of cannabinol derivatives, differences in affinity results on mouse CB 2 R and human CB 2 R were reported [144,145]. The authors suggest the existence of different binding motifs of cannabilactones for the mouse or human CB 2 R [144].…”
Section: Affinity and Species Differencementioning
confidence: 99%
“…From these findings, CB 2 -selective agonists are potential therapeutics for itch and pain without undesirable effects on the CNS. Indeed, several CB 2 -selective agonists with analgesic effects have been reported on [11,12,13,14,15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, many studies have reported that (R)-(ϩ)- [2,3-dihydro-5-methyl-3-(4-morpholinylmethyl) pyrrolo-[1,2,3-d,e]-1,4-benzoxazin-6-yl]-1-naphthalenyl-methanone (WIN55,212) evokes antinociception and antihyperalgesia via the G protein-coupled CB1 receptor using pharmacological blockade or gene deletion studies (Zimmer et al, 1999;Johanek et al, 2001;Johanek and Simone, 2004;Agarwal et al, 2007). In addition, the antihyperalgesic properties of (2-iodo-5-nitrophenyl)-[1-(1-methylpiperidin-2-ylmethyl)-1H-indol-3-yl]-methanone (AM1241) and cannabilactones have been attributed exclusively to the CB2 receptor (Malan et al, 2001Ibrahim et al, 2003Ibrahim et al, , 2005Quartilho et al, 2003;Gutierrez et al, 2007;Khanolkar et al, 2007). However, recent studies have demonstrated an alternative mechanism by which cannabinoids modulate nociceptive transmission via ionotropic receptors.…”
Section: Introductionmentioning
confidence: 99%